HONES THE CHARACTER OF DISCIPLINE AND RESPONSIBILITY OF STUDENTS THROUGH RO'AN ACTIVITIES AT THE WALISONGO PUTRA ISLAMIC BOARDING SCHOOL - Awabin, Muhammad Ramdan; Kibtiyah, Asriana (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Education is a very important foundation and plays a strategic role in fostering families, communities, and nations, the application of Santri education is based on character or behavior, namely discipline, and responsibility. Discipline is a person's awareness to act, while responsibility is the action to be taken. To hone the character of discipline and responsibility of the students, Islamic boarding schools hold ro'an activities or community service to train them to move and show concern for the environment. The purpose of this study is to describe the formation of the character of discipline and responsibility of students through ro'an activities at the Walisongo Putra Islamic Boarding School. This study uses a qualitative approach with a descriptive model. Based on the findings in the field, ro'an activities at the Walisongo Putra Islamic Boarding School are carried out by community service, namely cleaning the cottage environment including bathrooms, mosques/musholla, kitchen room, administrators' rooms, courtyards, and students' bedrooms so that they are clean and comfortable to use while studying.